A unique subtype of ramified microglia associated with synapses in the rat hippocampus. (2nd July 2021) - Ohgomori, Tomohiro; Iinuma, Kyoko; Yamada, Jun; Jinno, Shozo
Abstract: To date, a number of studies have reported the heterogeneity of activated microglia. However, there is increasing evidence suggests that ramified, so‐called resting, microglia may also be heterogeneous, and they may play diverse roles in normal brain homeostasis. Here, we found that both 5D4 keratan sulfate epitope‐positive (5D4 + ) and 5D4‐negative (5D4 ‒ ) microglia coexisted in the hippocampus of normal rats, while all microglia were negative for the 5D4 epitope in the hippocampus of normal mice. We thus aimed to determine the potential heterogeneity of microglia related to the 5D4 epitope in the normal rat hippocampus. The optical disector analysis showed that the densities of 5D4 + microglia were higher in the stratum oriens of the CA3 region than in other layers and regions. Although both 5D4 + and 5D4 ‒ microglia exhibited a ramified morphology, the three‐dimensional reconstruction analysis showed that the node numbers, end numbers, and complexity of processes were higher in 5D4 + than in 5D4 ‒ microglia. The linear discriminant analysis showed that 5D4 + and 5D4 ‒ microglia can be classified into distinct morphometric subtypes. The ratios of contact between synaptic boutons and microglial processes were higher in 5D4 + than in 5D4 ‒ microglia. The gene expressions of pro‐inflammatory cytokine interleukin‐1β and purinergic receptor P2Y12 (P2Y12 R) were higher in 5D4 + than in 5D4 ‒ microglia. Together, these results indicate that at least two different subtypes of ramified microglia coexist in the normal rat hippocampus and also suggest that 5D4 + microglia may represent a unique subtype associated with synapses. Abstract : Both 5D4 keratan sulfate epitope‐positive (5D4 + ) and 5D4‐negative (5D4 ‒ ) ramified microglia coexisted in the hippocampus of normal rats. The ratios of contact between synaptic boutons and microglial processes were higher in5D4 + than in 5D4 ‒ microglia. The present study suggests that 5D4 + ramified microglia in the hippocampus of normal rats may represent a unique subtype associated with synapses.